2020
DOI: 10.1002/adsc.202001324
|View full text |Cite
|
Sign up to set email alerts
|

Rhodium‐Catalyzed Regioselective 3‐Fluoroallylic Cyanation

Abstract: A rhodium catalyzed allylic cyanation of 3‐fluoroallylic trifluoroacetates with TMSCN and a bulky phosphite ligand gives 3‐fluoroallylic nitriles with a good substrate scope and high Z/E‐selectivity. For dialkylated substrates the fluorine substituent controls the regioselectivity in favor of the distal product. For the stereoselectivity of the allylic cyanation selected scalemic substrates showed inversion of the stereocenter and some or no stereoerosion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…An allylic rhodium cyanation of 3‐fluoroallylic trifluoroacetates ( 63 ) for the preparation of 3‐fluoroallylic nitriles ( 65 ) was described by Middel and colleagues (Scheme 33). [ 53 ] Initial investigation was carried out by using 3‐fluoroallyl carbonate as model substrate. Then authors screened the reaction of trifluoroacetate and concluded 5 equiv.…”
Section: Classificationmentioning
confidence: 99%
“…An allylic rhodium cyanation of 3‐fluoroallylic trifluoroacetates ( 63 ) for the preparation of 3‐fluoroallylic nitriles ( 65 ) was described by Middel and colleagues (Scheme 33). [ 53 ] Initial investigation was carried out by using 3‐fluoroallyl carbonate as model substrate. Then authors screened the reaction of trifluoroacetate and concluded 5 equiv.…”
Section: Classificationmentioning
confidence: 99%